2007
DOI: 10.2527/jas.2006-610
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between the prion protein locus and udder morphology traits and milk yield in Sardinian sheep1,2

Abstract: Different approaches were applied to investigate prion protein (PrP)-encoding gene effects on udder morphology and milk yield in Sardinian sheep. The PrP genotype of 23,077 animals (10,029 males) was determined. The direct effect of the PrP or a closely linked gene was analyzed at the population-wide level using 2 animal models, based on records from genotyped animals, including only the PrP genotype as a fixed effect. In the female model, the dependent variable was animal performance deviation, calculated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…As such a selection programme can potentially have negative effects on certain production traits in particular breeds, we aimed here to determine the frequencies of PrP alleles and genotypes in Bovška sheep and evaluate their possible associations with milk production and composition traits. The frequency of the most frequent allele ARQ (57.14 %) is comparable with the frequencies found in other continental breeds (SALARIS et al 2007, VAN KAAM et al 2005, CASELLAS et al 2006, WISNIEWSKA et al 2006, although higher proportion of ARQ allele was found in the neighbouring Italian province Veneto (68.0 %, DE MARCHI et al 2005), in the Spanish Churra sheep (75.9 %, ALVAREZ et al 2006) and certain Northern German breeds (DRÖGEMÜLLER et al 2001). The proportions of the desired ARR allele found in other continental breeds were mostly higher than in Bovška sheep (17.12 %), from 18.2 % in the Spanish Churra sheep (ALVAREZ et al 2006) to 42.5 % in the Sardinian sheep (SALARIS et al 2007).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…As such a selection programme can potentially have negative effects on certain production traits in particular breeds, we aimed here to determine the frequencies of PrP alleles and genotypes in Bovška sheep and evaluate their possible associations with milk production and composition traits. The frequency of the most frequent allele ARQ (57.14 %) is comparable with the frequencies found in other continental breeds (SALARIS et al 2007, VAN KAAM et al 2005, CASELLAS et al 2006, WISNIEWSKA et al 2006, although higher proportion of ARQ allele was found in the neighbouring Italian province Veneto (68.0 %, DE MARCHI et al 2005), in the Spanish Churra sheep (75.9 %, ALVAREZ et al 2006) and certain Northern German breeds (DRÖGEMÜLLER et al 2001). The proportions of the desired ARR allele found in other continental breeds were mostly higher than in Bovška sheep (17.12 %), from 18.2 % in the Spanish Churra sheep (ALVAREZ et al 2006) to 42.5 % in the Sardinian sheep (SALARIS et al 2007).…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, PrP genotype did not significantly affect any milk trait in the Spanish Churra (ALVAREZ et al 2006) and in the East Friesian dairy sheep (DE VRIES et al 2005). However, the ARR homozygotes in Sardinian sheep produced lower milk yields (P<0.05) than ARR heterozygotes or other genotypes (SALARIS et al 2007). Thus, selection for the resistant ARR alleles could result in negative effects on milk productivity in Sardinian sheep.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…There was no indication in any of the populations studied that there was an association between PrP genotype and milk yield, percentage fat, or percentage protein. Similarly, there was no evidence for an association between PrP genotype and the udder morphology traits: teat position, degree of udder suspension, udder depth, and degree of separation of two udder halves [72].…”
Section: Association Between the Prp Gene And Milk Production Traitsmentioning
confidence: 86%